2023
DOI: 10.2147/ijgm.s393233
|View full text |Cite
|
Sign up to set email alerts
|

The Burden of Sickle Cell Disease in Saudi Arabia: A Single-Institution Large Retrospective Study

Abstract: Purpose Sickle cell disease (SCD) is a significant burden for patients and healthcare systems due to multiple factors, including high readmission rates. This study aimed to determine the general characteristics, etiology of admissions, annual admission rate, length of stay, and readmission rate of patients with SCD. Patients and Methods This retrospective observational study included all adult patients with SCD admitted to the General Internal Medicine (GIM) unit betwee… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2023
2023
2025
2025

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 14 publications
(8 citation statements)
references
References 24 publications
0
5
0
Order By: Relevance
“…Despite the fact that healthcare is free of charge in Saudi Arabia, SCD has a significant economic burden on Saudi society as well as an impact on the patient’s quality of life. 17 Therefore, launching a premarital screening program is justified in this area. 7 , 10 …”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Despite the fact that healthcare is free of charge in Saudi Arabia, SCD has a significant economic burden on Saudi society as well as an impact on the patient’s quality of life. 17 Therefore, launching a premarital screening program is justified in this area. 7 , 10 …”
Section: Discussionmentioning
confidence: 99%
“…Despite the fact that healthcare is free of charge in Saudi Arabia, SCD has a significant economic burden on Saudi society as well as an impact on the patient's quality of life. 17 Therefore, launching a premarital screening program is justified in this area. 7,10 In our study, we found that the majority of the participants were aware of SCD's mode of inheritance and pain as the main (and frequent) presentation of the disease.…”
Section: Discussionmentioning
confidence: 99%
“…The average utilization of healthcare facilities by the enrolled SCD patients was defined as one admission per year and four ED visits per year. 3 Based on this, two categories were established. The high utilization group whose number of admissions or ED visits per year exceeded the previously defined average, and the low utilization group had admissions or ED visits that were equal to or lower than the defined average.…”
Section: Methodsmentioning
confidence: 99%
“…A retrospective study showed that Saudi patients with SCD have a high rate of emergency department (ED) visits, admissions, and readmissions. 3 Similarly, another study on the Saudi SCD population showed that 64.3% had three or more ED visits related to SCD over six months. It was found that male gender, being married, and having a university degree are risk factors for a higher rate of ED visits.…”
Section: Introductionmentioning
confidence: 95%
“…According to the Saudi Premarital Screening Program, sickle cell gene prevalence is estimated to be 4.2% for sickle cell trait and 0.26% for SCD in the adult population. The Eastern province has the highest prevalence rates, approximately 17% for sickle cell trait and 1.2% for SCD [ 3 , 4 ].…”
Section: Introductionmentioning
confidence: 99%